Synthesis of aniline-based menthol glycinates and derivatives - Joseph E. Mathews; Jacob C. Hood; Douglas A. Klumpp (Results in Chemistry, 2022)
A series of aniline-based menthol glycinates have been prepared in two steps from L-menthol. It is shown that the aniline-based menthol glycinates are themselves a useful scaffold leading to amide, carbamate, sulfonamide, and urea structures.